Finger grip relaxation as therapeutic for reducing headache scale in hypertension cases - Maria, Dely (International Journal Of Community Medicine And Public Health, 2022)
The purpose of this case study is to see the extent to which the application of finger grip relaxation in reducing headache in clients who have hypertension problems. The research design used is descriptive research with case study method. Participants in this study used two clients who had the same nursing problems and medical problems, namely hypertension with headache problems. The action was carried out for 8 visits. After the finger grip relaxation was carried out on both subjects, there was a decrease in the pain scale and blood pressure. Complaints of difficulty sleeping can also be controlled. This finger grip relaxation therapy can reduce blood pressure, pain scale, and relieve symptoms experienced by people with hypertension. Finger grip reflexes will work effectively if the emphasis on the indicated point is appropriate, the time is consistent, and there is cooperation between the two when applying finger grip relaxation therapy.